Charter Schools and Race: A Lost Opportunity for Integrated Education - Frankenberg, Erica; Lee, Chungmei (Education Policy Analysis Archives, 2003)
Segregation patterns in the nation's charter schools are studied. After reviewing state charter legislation that directly addresses issues of racial and ethnic balance of student enrollment, we briefly examine the racial composition and segregation of the charter school population nationally. School-level analyses, aggregated by state constitute the primary method of studying segregation in charter schools. First, we look at racial composition and segregation of charter schools by state. Then, we consider the differences in segregation between non-charter public schools (or simply "public schools" for convenience) and charter schools, as well as segregation within the charter school sector. We conclude with a discussion of the article's findings and recommendations to promote further racial equity in this growing sector of public schools.